Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=6.34.8+24.2.45+12.21.4\)
\(A=48.34+48.45+48.21\)
\(A=48.\left(34+45+21\right)\)
\(A=48.100\)
\(A=4800\)
a) 6 x 34 x 8 + 24 x 2 x 45 + 12 x 21 x 4
= 48 x 34 + 48 x 45 + 48 x 21
= 48 x ( 34 + 45 + 21 )
= 48 x 100
= 4800
b) 45 x 16 + 55 x 17
= 5 x 9 x 16 + 5 x 11 x 17
= 5 x 144 + 5 x 187
= 5 x ( 144 + 187 )
= 5 x 331
= 1655
\(A=\frac{2009.2010-2}{2008+2008.2010}=\frac{\left(2008+1\right).2010-2}{2008+2008.2010}\)
\(=\frac{2008.2010+2010-2}{2008+2008.2010}=\frac{2008.2010+2008}{2008+2008.2010}=1\)
\(B=\frac{-2009.20102010}{20092009.2010}=\frac{-2009.2010.10001}{2009.10001.2010}=-1\)
Vậy A + B = 1 + (-1) = 0
\(A=\frac{2009.2010-2}{2008+2008.2010}=\frac{\left(2008+1\right).2010-2}{2008+2008.2010}\)
\(=\frac{2008.2010+2010-2}{2008+2008.2010}=\frac{2008.2010+2008}{2008+2008.2010}=1\)
\(B=\frac{-2009.20102010}{20092009.2010}=\frac{-2009.2010.10001}{2009.10001.2010}\)
Vậy A + B = 1 + (-1) = 0
Ta có : \(A=\frac{2009.2010-2}{2008+2008.2010}>0\)
\(B=\frac{-2009.20102010}{20092009.2010}< 0\)
Nên A > B
Ta có :
\(A=\frac{2009.2010-2}{2008+2008.2010}\)
\(A=\frac{\left(2008+1\right).2010-2}{2008.\left(1+2010\right)}=\frac{2008.2010+2008}{2008.2011}\)
\(A=\frac{2008.\left(1+2010\right)}{2008.2011}=\frac{2008.2011}{2008.2011}=1\)
\(B=\frac{-2009.20102010}{20092009.2010}=\frac{\left(-2009\right).2010.10001}{2009.10001.2010}=\frac{-2009}{2009}=-1\)
Vậy \(A+B=1+\left(-1\right)=0\)
\(A=\frac{2009\cdot2010-2}{2008+2008\cdot2010}=\frac{\left(2008+1\right)\cdot2010-2}{2008+2008\cdot2010}=\frac{\left(2008\cdot2010\right)+\left(2010-2\right)}{2008+2008\cdot2010}=\frac{2008\cdot2010+2008}{2008+2008\cdot2010}=1\)\(B=\frac{-2009\cdot20102010}{20092009\cdot2010}=\frac{-2009\cdot2010\cdot10001}{2009\cdot10001\cdot2010}=-1\)
=>A+B=1+(-1)=0
Vậy A+B=0
\(A=\frac{2009.2010-2}{2008+2008.2010}=\frac{2008.2010+2010-2}{2008+2008.2010}=\frac{2008.2010+2008}{2008+2008.2010}=1\)
\(B=\frac{-2009.20102010}{20092009.2010}=\frac{-2009.2010.10001}{2009.10001.2010}=-1\)
Vậy \(a+b=1+\left(-1\right)=0\)
A=\(\frac{2009.2010-2}{2008+2008.2010}=\frac{\left(2008+1\right).2010-2}{2008+2008.2010}\)
\(=\frac{2008.2010+2010-2}{2008+2008.2010}\)
\(=\frac{2008.2010+2008}{2008+2008.2010}=1\)
B=\(\frac{-2009.20102010}{20092009.2010}=\frac{-2009.2010.10001}{2009.10001.2010}=-1\)
Vậy A+|B= 1+(-1)=0